Regulatory Innovation Strategy Achieving A Future Vision In Reform To Reduce Tax Evasion And The Ambition Of The General Authority For Taxes In Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Studying the organizational innovation strategy in the General Authority for Taxes is of great importance to those concerned with financial affairs for the purpose of strengthening tax work in achieving tax justice and reducing tax evasion. Establishing this work is the ambition of the General Authority for Taxes on precise scientific and technical foundations, because there is a loss of confidence between the taxpayer and the tax administration. It prompts some taxpayers to refrain from submitting credible tax accounts, and from here the research problem can be formulated It is: Does the General Authority for Taxes in Iraq not rely on the strategy of organizational innovation lead to tax evasion? To achieve the goal of the research, it is to identify the role that the administration of the General Authority for Taxes plays in implementing the strategy of organizational innovation through ways and procedures to reduce tax evasion to achieve the ambition of the General Authority. For taxes in tax justice and increasing tax revenues, and based on the research problem, two basic research hypotheses were tested: The first main hypothesis: Is there a relationship between the organizational innovation strategy and tax evasion, and the second main hypothesis: Is there an effect of the organizational innovation strategy on tax evasion in reducing it?. The research concluded with what the results of the study showed. The General Tax Authority used a strategy of regulatory innovation for large-scale data through the tremendous speed in processing it and obtaining useful information in reducing tax evasion. In addition to implementing appropriate legal legislation, the most important recommendations that were reached through the theoretical and practical aspects of the study were presented regarding the need for government agencies to support the concept and importance of applying the organizational innovation strategy among citizens and employees.